Relation Between Musculoskeletal Symptoms and Ergonomic Risk Assessment Among Mechanics at Car Service Centre: NMQ and REBA - Mohd Zaki, Nurul Elyna Asyiqen; Abdol Rahman, Mohd Nasrull; Kamarudzaman, Mazlina (Research Progress in Mechanical and Manufacturing Engineering, 2022)
One of the most occupational diseases is related to Musculoskeletal Disorders (MSDs) which mainly affects the lower back pain, neck and upper and lower extremities and this research highlights the relationship between Musculoskeletal Symptoms (MSS) and Ergonomic Risk Assessment (ERA) among mechanics at car service centre. This study focuses on three objectives which are the musculoskeletal symptoms among mechanics at car service centre using Nordic Musculsokeletal Questionnaire (NMQ), the level of ergonomic risk assessment using Rapid Entire Body Assessment (REBA) method, and the relationship between NMQ and REBA. This cross-sectional study was conducted among mechanics (male : 40; age : ≥20yrs) from eleven selected workshops in Perak. Data were collected using a structured questionnaire consist of demographic questions, NMQ for MSDs assessment and REBA method for ergonomic assessment. Based on the survey that had been done, the results showed that the highest and the least reported Musculoskeletal Symptoms is lower back with a percentage 62.5% and neck with a percentage 45% respectively. REBA score also showed that further investigation needed as the results showed that 60% has medium risk and 17.5% of them are high risk.